PERANAN IKLAN TERHADAP PENGEMBANGAN UMKM PENGOLAHAN PANGAN DI KOTA YOGYAKARTA - , IVAN ADI PRABOWO, Dr. Ir. Slamet Hartono, S.U., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Generally every UMKM (The micro, small medium business), either run the business by making goods or by servicing, definitely will always want the products are recognized widely in every level in society. Through advertisement, a product can be recognized, loved, and wanted by the society. This is caused by the remarkable potential of an advertisement to influence as well as to form public opinion and perseption. The limitedness of area in city makes the government of Yogyakarta shift the agriculture development basis from urban system into city system, it is agribusiness which focuses on processing and marketing agricultural product. This research is aimed to find out the form of the advertising media and the role of the advertisement in the profit of food processing UMKM in Yogyakarta. The research areas are spread in 14 subdistricts located in Yogyakarta, UMKMs which are analysed in each subdistrict more less are 3 â 4 UMKMs with the criteria based on the advertisement media that is used. The data which are collected is about the perseption of the role of advertisement towards the food processing UMKM which is in form of profit. The basic method which is used in the research is the descriptive method. The sample used in this research was nonrandom sampling/nonprobability sampling. The data collecting technics are done by observations, interviews, data entry, documentations, and bibliographies. The data sources which are used in the research are primary source, 45 respondents, and also secondary source. Data analysis which are used are descriptive analisys, reliability and validity tests, and also hipothesis tests. The result of the research shows that most of food processing UMKM in Yogyakarta are street vendors. Some advertising media which are used are printed and electronic medias. The printed medias which are used such as newspapers, billboards, posters, and banners, while the electronics medias which are used such as radio, and televisions. The advertisement media by banners is the most favorite. The hipothesis testings through the Pearson correlation resulting in r = 0.541 with the significance level = 0,05 and the probability 0,00012 (smaller than 0,05). This shows the relation between advertising perseption and the profit. The suggestion for the research is that the UMKM's manager does not have to doubt in using advertisement, because advertisement has important roles in the development and progress of a company.